Short-Season Corn Cost-Return Budget in Southeast Kansas - Fausett, Marvin R. (My University, 1996)
This publication outlines the expected costs and returns for short-season corn in southeast Kansas.
MF993_1996_10
Keywords: MF993; Economics; Crops; MF